Strengthening Students' Mental Resilience and Character in the Era of Digital Disruption through the Al-Khidmah Dzikir Assembly - Fatikhul Anwarul Umam; Khotimah Suryani; Mokhamad Ali Musyafa (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2026)
The era of digital disruption presents various challenges for students, not only in academic aspects but also in character building and mental resilience. The intense use of digital technology, academic pressure, and various rapid social changes have the potential to increase stress, anxiety, and weaken the internalization of character values ​​among students. Therefore, an educational approach is needed that is not only oriented towards intellectual development, but also able to strengthen the spiritual and psychological dimensions of students. This study aims to analyze the role of Majlis Dzikir Al-Khidmah in building mental resilience and character of students in the era of digital disruption. The study used a qualitative approach with a case study design conducted at the Islamic University of Darul Ulum (UNISDA) Lamongan. Data were collected through in-depth interviews, participatory observation, and documentation involving supervisory lecturers, Majlis Dzikir Al-Khidmah administrators, and active student participants. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the Al-Khidmah Dhikr Assembly plays an effective role in internalizing the values ​​of religiosity, istiqamah, discipline, responsibility, humility, patience, and social concern through a continuous spiritual habituation process. Furthermore, student involvement in the dhikr assembly contributes to strengthening mental resilience, characterized by increased emotional regulation, reduced overthinking, increased inner peace, and the ability to deal with academic pressure more adaptively. These findings expand the study of spirituality-based character education by demonstrating that collective dhikr practices function not only as a medium for moral formation but also as a mechanism for strengthening students' mental resilience. This study concludes that the Al-Khidmah Dhikr Assembly is a relevant spiritual education model in supporting student character development and mental health in the digital era. Further research is recommended to use a mixed methods approach and involve a broader scope of research to test the effectiveness of this model in various higher education contexts.